Yield of different white button strains in sugar cane by product-based composts - Jesus, João Paulo Furlan de; Kohori, Carolina Bugalho; Andrade, Meire Cristina Nogueira de [UNESP]; Minhoni, Marli Teixeira de Almeida (My University, 2013)
The production of quality compost for Agaricus bisporus using alternative and local agricultural wastes beyond the search for productive strains are among the main factors related to improve yield. Thus, we evaluated the effect of compost nitrogen supplementation type using two compost formulation based on sugar cane by-products such as straw and bagasse as raw materials: (1) classic compost using chicken manure and (2) synthetic compost using soybean bran, urea and ammonium sulfate, for the cultivation of the five strains of A. bisporus: ABI-05/03, ABI-04/02, ABI-06/05, and ABI-09/10 ABI-09/11. We found that the classic compost obtained average temperature and mass loss of 10.56 and 13.29% higher than the synthetic compost, respectively, during the composting, pasteurization and conditioning process. The classic compost achieved greater yield in the end of 25 days of harvest by the strains ABI-05/03, ABI-06/05 and ABI-04/02 corresponding to 26.78, 25.34 and 24.71%, respectively. We concluded that the classic and synthetic, based on sugar cane straw and bagasse are suitable agricultural waste for A. bisporus cultivation and the classic compost obtained higher composting temperatures in relation to synthetic compost, corroborating higher yields and more defined-pattern cultivation cycle for all strains when grown in classic compost.
Keywords: Agaricus bisporus; By-products; Supplementation; Classic; Synthetic